Assembly and Care of Memory: Placing Objects and Hybrid Media to Revisit International Expositions. (1st April 2019) - Minner, Jennifer
Abstract: The bowerbird assembles and fastidiously cares for displays of found objects. The bowerbird actions are a metaphor that illustrate the deep connections between humans and objects in communicating about places and the past. This article presents three vignettes of artists and history advocates interpreting former international expo, or world's fair, sites. The first vignette discusses Jonathan Jones' barrangal dyara (skin and bones) a large‐scale public art installation in Sydney, Australia. A second focuses on narrations in the landscape and on a YouTube channel of objects and sites associated with memories and remnants of Expo '88, in Brisbane, Australia. A third example is Lost Utopias, by Jade Doskow, a series of large‐format photographs of 19th and 20th century expo sites. Each reveals human connections to objects and to landscapes, the power of reinterpretations generated out of assemblies of objects, and the hybrid places constructed out of multiple media.